SIMBOL KEJAYAAN PERKEBUNAN TEH DI INDONESIA: KASUS BANGUNAN BEKAS PABRIK TEH GUNUNG MAS 1910 DI CISARUA, BOGOR - Lia Nuralia (JURNAL PANALUNGTIK, 2019)
The building of the former Gunung Mas Tea Factory in Cisarua Bogor can provide important information about tea commodities in the past. However, it is feared that it will experience changes in its function and form, so its existence needs to be written down. The purpose of this paper is to describe the symbol of the glory of tea plantations in Indonesia during the Dutch East Indies era, with the case of the former Gunung Mas tea factory. The research method used is descriptive analytical method with interpretation, using a symbolic meaning approach and historical approach, by applying non-verbal communication concept. The results obtained were that factory buildings became a symbol of the glory of tea commodities in the past. The glory is reflected in the physical fruition of flowers and its components show greatness and splendor, which can be interpreted as a symbol of the glory of tea commodities in the past.Key words: Symbol of glory, former tea factory of Gunung Mas, Cisarua-Bogor